2020
DOI: 10.1111/dgd.12657
|View full text |Cite
|
Sign up to set email alerts
|

Developmental regulation of olfactory circuit formation in mice

Abstract: In mammals, odorants induce various behavioral responses that are critical to the survival of the individual and species. Binding signals of odorants to odorant receptors (ORs) expressed in the olfactory epithelia are converted to an odor map, a pattern of activated glomeruli, in the olfactory bulb (OB). This topographic map is used to identify odorants for memory-based learned decisions. In the embryo, a coarse olfactory map is generated in the OB by a combination of dorsal-ventral and anterior-posterior targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 84 publications
(134 reference statements)
1
30
0
Order By: Relevance
“…Figure 1 shows the structure of the rodent OB as an anatomical model for reference. Although we do not go deeper into detail in this review, there are many excellent reviews summarizing the cell types, synapses, and neuronal circuits found in the MOB ( Shepherd et al, 2004 ; Wachowiak and Shipley, 2006 ; Figueres-Onate et al, 2014 ; Imai, 2014 ; Nagayama et al, 2014 ; Sakano, 2020 ). Briefly, the OSN axons run tangentially through the olfactory nerve layer (ONL) at the surface of the OB before entering the glomerular layer (GL) ( Klenoff and Greer, 1998 ; Rodriguez-Gil et al, 2015 ).…”
Section: Basic Neural Circuitry Of the Mammalian Olfactory Systemmentioning
confidence: 99%
“…Figure 1 shows the structure of the rodent OB as an anatomical model for reference. Although we do not go deeper into detail in this review, there are many excellent reviews summarizing the cell types, synapses, and neuronal circuits found in the MOB ( Shepherd et al, 2004 ; Wachowiak and Shipley, 2006 ; Figueres-Onate et al, 2014 ; Imai, 2014 ; Nagayama et al, 2014 ; Sakano, 2020 ). Briefly, the OSN axons run tangentially through the olfactory nerve layer (ONL) at the surface of the OB before entering the glomerular layer (GL) ( Klenoff and Greer, 1998 ; Rodriguez-Gil et al, 2015 ).…”
Section: Basic Neural Circuitry Of the Mammalian Olfactory Systemmentioning
confidence: 99%
“…In the mouse olfactory system, about one thousand types of olfactory sensory neurons (OSNs) convey odor information perceived in the olfactory epithelium (OE) to the olfactory bulb (OB). Each OSN expresses a single type of G protein-coupled odorant receptor (OR), and same-type OSNs expressing the same OR extend axons that converge onto common individual target sites called glomeruli in the olfactory bulb [ 100 ]. As the organization of glomeruli does not correlate with the position of the OSNs in the OE, convergence of olfactory axons onto specific glomeruli along the antero-posterior axis is ensured by pre-target axon sorting ( Figure 2 B).…”
Section: Trans-axonal Repulsionmentioning
confidence: 99%
“…In the mouse olfactory system, for instance, olfactory axons are segregated along the dorso-ventral axis and maintain their relative position from their exit from the OE to their entry of the OB. Axons from the dorsomedial zone of the OE project to the dorsal part of the OB first and are followed by axons from the ventrolateral zone that project to the ventral OB [ 100 , 118 , 119 ]. Interestingly, Sema3F and its receptor Neuropilin-2 (Nrp2) are expressed in a complementary graded manner along the dorso-ventral axis in OSNs.…”
Section: Trans-axonal Repulsionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports further suggest that topographic organization occurs before the growth cone reaches the target tissue (Imai et al, 2009;Sakano, 2020). In olfactory sensory neurons (OSNs), complementary expression of the axon-guidance receptor Neuropilin-1 and its repulsive ligand Semaphorin-3A leads to pre-target axon segregation and topography based on relative protein levels (Imai et al, 2009;Sakano, 2020). Gain-and loss of function of one of those molecules specifically in OSNs leads to abnormalities in pre-target axon sorting by shifting axons from the Neuropilin-1 high bundle to the Neuropilin-1 low bundle, or vice versa.…”
Section: Introductionmentioning
confidence: 99%